Penatalaksanaan Holistik Pasien Vertigo Pada Ny. S Umur 34 Tahun Di Puskesmas Campang Raya Melalui Pendekatan Kedokteran Keluarga - Yulia Puspita Sari; Zuraida, Reni (CV. Jasa Sukses Abadi, 2023)
Vertigo is a term that comes from the Latin, vertere, which means twisting. In general, vertigo is known as an illusion of movement or a hallucination of movement. Vertigo is found in the form of complaints in the form of a sense of spinning or a sense of moving from the surrounding environment (circular vertigo) but sometimes complaints are also found in the form of a feeling of being pushed or pulled away from the vertical plane (vertical linear). Apply a holistic and comprehensive approach to family doctors in detecting risk factors, clinical problems, and patient management based on evidence based medicine and is family- approached and patient-centered. Primary data were obtained through anamnesis, physical examination, supporting examinations and home visits to assess the physical environment. Mrs. S, 34 years old, came to the Campang Raya Community Health Center with complaints of dizziness since two days before coming to the Puskesmas. Spinning dizziness arises suddenly, is felt continuously and gets worse when the patient raises his head to sit or stand after sleeping. Complaints accompanied by nausea, vomiting, and cold sweats. Complaints have been repeated and the first time was felt six years ago. The patient's concern is that the complaint gets heavier and interferes with daily activities. The patient was diagnosed with vertigo based on history and physical examination. A holistic management has been carried out with the approach of a family doctor, through non-medical and medical interventions were carried out on patients and their families with education related to the patient's illness in three home visits. The evaluation results obtained were reduced patient complaints and increased knowledge of patients and their families regarding vertigo.